2006
DOI: 10.1002/ptr.1932
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potentials of Iranian Carica papaya juice in vitro and in vivo are comparable to α‐tocopherol

Abstract: Carica papaya is widely cultivated throughout the world and is used as a food and also as a traditional medicine, particularly as an antiseptic and contraceptive. The present study was designed to explore the toxicological and antioxidant potential of dried C. papaya juice in vitro and in vivo. The oral LD(50) of the juice of C. papaya was determined, and the antioxidant potentials determined by DPPH and FRAP tests. In vivo examination was performed after oral administration of dried papaya juice to rats for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…This degradation effect is due to the presence of the cysteine protease papain [21]. Papaya is also very used in the traditional medicine, particularly as an antiseptic and contraceptive [22] and wound care [23]. In a recent report [24], Collard and Roy provide evidences that the wound diabetic mouse model benefits from a fermented papaya supplementation that specifically influences the response of wound-site macrophages and subsequent angiogenic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…This degradation effect is due to the presence of the cysteine protease papain [21]. Papaya is also very used in the traditional medicine, particularly as an antiseptic and contraceptive [22] and wound care [23]. In a recent report [24], Collard and Roy provide evidences that the wound diabetic mouse model benefits from a fermented papaya supplementation that specifically influences the response of wound-site macrophages and subsequent angiogenic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro evaluation of the antioxidant effects of papaya showed that the highest antioxidant activity (80%) was observed with a concentration of 17.6 mg/mL. This preliminary study indicates the safety and antioxidative stress potential of the juice of papaya, which was found to be comparable to the standard antioxidant compound alpha-tocopherol (Mehdipour et al, 2006). The study conducted by da Silva et al (2010) further supports the notion that papain, the compound isolated from the latex of unripe C. papaya is a promising source of potential antioxidant.…”
Section: Anxiolytic and Antioxidant Activitymentioning
confidence: 52%
“…In vitro evaluation of the antioxidant effects of papaya showed that the highest antioxidant activity 80% was observed with a concentration of 17.6 mg/ml (Jaiswal, et al, 2010). Blood lipid peroxidation levels decreased significantly after administration of all doses of papaya juice (100, 200, 400 mg/kg/day) to 35.5, 39.5 and 40.86% of the control, respectively, compared with a value of 28.8% for vitamin E (Mehdipour, et al, (2006). The blood total antioxidant power was increased significantly by all doses of papaya juice (100, 200, 400 mg/kg/day) to 11.11, 23.58 and 23.14% of the control, respectively.…”
Section: Antioxidant Activitymentioning
confidence: 86%
“…Several studies showed that phenolic compounds are the major bioactive phytochemicals with human health benefits (Swathi, et al, 2016). Mehdipour, et al (2006) explored the toxicological and antioxidant potential of dried Carica papaya juice in vitro and in vivo. In vivo examination was performed after oral administration of dried papaya juice to rats for 2 weeks at doses of 100, 200 and 400 mg/kg (Jaiswal, et al, 2010).…”
Section: Antioxidant Activitymentioning
confidence: 99%